Isolation of Pteropine orthoreovirus from Pteropus vampyrus in Garut, Indonesia - Takemae, Hitoshi; Basri, Chaerul; Mayasari, Ni Luh Putu Ika; Tarigan, Ronald; Shimoda, Hiroshi; Omatsu, Tsutomu; Supratikno; Pramono, Didik; Cahyadi, Danang Dwi; Kobayashi, Ryosuke; Iida, Keisuke; Mizutani, Tetsuya; et al. (Virus genes, 2018)
Flying foxes belonging to the genus Pteropus are known to be reservoirs of zoonotic viruses. In this study, we describe the isolation of Pteropine orthoreovirus (PRV) from rectal swab samples of Pteropus vampyrus in Indonesia. PRV is an emerging zoonotic respiratory virus that can be transmitted from bats to humans. Rectal swabs (n = 91) were screened by PCR for PRV and 10 (11%) were positive. Phylogenetic analysis based on nucleotide sequences indicated that the S2, S3, S4, M3, L2, and L3 segments of one isolate (Garut-69) were closely related to previously isolated strains in Indonesia. The remaining gene segments showed both similarity and genetic divergence with other PRV strains, suggesting that re-assortment events had occurred. This is the first report of PRV infection to P. vampyrus in West Java, Indonesia.